Zika virus outbreak in 19 English- and Dutch-speaking Caribbean countries and territories, 2015-2016 - Lorraine Francis; Shelly-Ann Hunte; Ann Marie Valadere; Karen Polson-Edwards; Virginia Asin-Oostburg; C. James Hospedales (Pan American Health Organization, 2018)
Surveillance for Zika virus was enhanced in the English- and Dutch-speaking Caribbean following emergence of the virus in Brazil in May 2015. The first autochthonous case of Zika in the Caribbean was reported by Suriname in November 2015, and the virus subsequently spread rapidly throughout the region. Caribbean Public Health Agency (CARPHA) member states (CMS) reported clinically suspected cases of Zika and submitted serum specimens to the agency for laboratory investigation. A patient was considered a confirmed case if Zika virus was detected by real-time reverse transcription-polymerase chain reaction (RT-PCR) assay or serological test. Due to the documented link between 1) Zika virus and congenital syndrome, and 2) Zika virus and Guillain-Barré syndrome (GBS), data on both of these disease outcomes were extracted from country and regional reports. This special report describes the epidemiology of laboratory-confirmed Zika cases reported to CARPHA, including links with both congenital syndrome and GBS, for 19 English- and Dutch-speaking Caribbean countries during the epidemic period (1 October 2015-29 December 2016).